(untitled) (Fiep Bulletin - online, 2013)
The open water swimming has grown very significantly in number of participants in recent years, with that, comes the need for more research on this type of solid proof and its effects on practitioners. Studies with athletes crossings are still limited in the literature, however, a variable that should be decisive for analysis of the magnitude of the requirements necessary for the successful accomplishment of these types of evidence is the estimated caloric expenditure based on this variable intensities and volumes training can be better adjusted to actual conditions of effort that athletes undergo, as well as nutritional requirements additional pre, during and post, proof can maximize the performance of the participants. The aim of the experiment was to examine the caloric expenditure of two proofs of open water distinct distances.A proof of Paulista championship open water with footage of 2.2 km and Marathon Swimming with 14 Bis 23 km away. The results indicates a high energy expenditure in the two tests, the 1st had average duration of 38 minutes and a caloric expenditure of 620 kcal, while the second had a mean duration of 8 hours and 30 minutes with a total caloric expenditure of 5346 kcal. The data demonstrate the great importance and concern mainly with feeding in the pre test and fluid and electrolyte during and post proof preserving the health of athletes and enhancing performance during the different types of evidence.